Antibacterial Activity of a Bioactive Tooth-Coating Material Containing Surface Pre-Reacted Glass in a Complex Multispecies Subgingival Biofilm - Caio Junji Tanaka; José Augusto Rodrigues; João Marcos Spessoto Pingueiro; Tatiane Tiemi Macedo; Magda Feres; Jamil Awad Shibli; Bruno Bueno-Silva (MDPI AG, 2023)
Bioactive materials were developed with the ability to release fluoride and provide some antimicrobial potential, to be widely used in dentistry today. However, few scientific studies have evaluated the antimicrobial activity of bioactive surface pre-reacted glass (S-PRG) coatings (PRG Barrier Coat, Shofu, Kyoto, Japan) on periodontopathogenic biofilms. This study evaluated the antibacterial activity of S-PRG fillers on the microbial profile of multispecies subgingival biofilms. A Calgary Biofilm Device (CBD) was used to grow a 33-species biofilm related to periodontitis for 7 days. The S-PRG coating was applied on CBD pins from the test group and photo-activated (PRG Barrier Coat, Shofu), while the control group received no coating. Seven days after treatment, the total bacterial counts, metabolic activity, and microbial profile of the biofilms were observed using a colorimetric assay and DNA-DNA hybridization. Statistical analyses were applied; namely, the Mann-Whitney, Kruskal-Wallis, and Dunn's post hoc tests. The bacterial activity of the test group was reduced by 25.7% compared with that of the control group. A statistically significant reduction was observed for the counts of 15 species: A. naeslundii, A. odontolyticus, V. parvula, C. ochracea, C. sputigena, E. corrodens, C. gracilis, F. nucleatum polymorphum, F. nucleatum vincentii, F. periodonticum, P. intermedia, P. gingivalis, G. morbillorum, S. anginosus, and S. noxia (p ≤ 0.05). The bioactive coating containing S-PRG modified the composition of the subgingival biofilm in vitro, thereby decreasing colonization by pathogens.